Complete mitochondrial genome sequence of Melipona scutellaris, a Brazilian stingless bee. (2nd September 2016) - Pereira, Ulisses de Padua; Bonetti, Ana Maria; Goulart, Luiz Ricardo; Santos, Anderson Rodrigues dos; Oliveira, Guilherme Correa de; Cuadros-Orellana, Sara; Ueira-Vieira, Carlos
Abstract: Melipona scutellaris is a Brazilian stingless bee species and a highly important native pollinator besides its use in rational rearing for honey production. In this study, we present the whole mitochondrial DNA sequence of M. scutellaris from a haploid male. The mitogenome has a size of 14, 862 bp and harbors 13 protein-coding genes (PCGs), 2 rRNA genes and 21 tRNA genes.